Penguatan Nilai Karakter dalam Cerita Anak “Little Abid Balita Cerdas & Saleh” Karya Tim Cordoba Kids - Muharrina Harahap (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This article examines the character values ​​contained in the children's story series "Little Abid Balita Cerdas & Saleh" by the Cordoba Kids Team. This children's story series consists of seven stories that tell the commendable behavior of a child named Abid. This character can be a role model for children, especially toddlers in planting character in a family. By using a qualitative descriptive method, the character values ​​contained in this children's story can be found, in relation to their representation in everyday life. The approach used in this study is the objective approach proposed by Abrams. Through this approach, the character values ​​contained in the seven series of children's stories will be seen through text structure analysis. Through the structure of the text, the character values ​​of the characters can be revealed. These values ​​include: divinity (religion), tolerance, honesty, compassion, generosity, respect for parents, courtesy, and cooperation. These character values ​​are very important in the pillars of children's character formation. These character values ​​are also a form of strengthening children's literacy in the family, especially at the age of toddlers.